Youth Outdoor Adventure Education Camps in China: Assessing Program Quality, Instructor Preparedness, and Stakeholder Satisfaction - Chen, Hongbing; Wang, Zhen; Wang, Xinghua (Technium Social Sciences Journal, 2025)
This study assesses the quality of youth outdoor adventure education (OAE) camps in China by examining program quality, instructor preparedness, and stakeholder satisfaction. Despite rapid market expansion from 77.8 billion yuan in 2021 to 354 billion yuan by 2024, systematic quality assessment of youth OAE camps remains limited. Using a mixed-methods approach, data were collected through site observations, instructor questionnaires (n=20), and youth surveys (n=90) across four representative camps during 2023-2024. Results reveal significant challenges across all three dimensions. Program quality suffers from aging infrastructure without standardized maintenance protocols, homogeneous curriculum dominated by traditional team-building activities, and seasonal operations limiting year-round access. Instructor preparedness shows substantial gaps: 75% are under age 35, only 30% hold relevant credentials in physical education or outdoor recreation, and formal OAE training is minimal. Stakeholder satisfaction remains moderate, with only 37.8% of youth satisfied with facilities, 44.4% satisfied with instruction, and 76.6% of parents supportive despite persistent safety concerns. These findings indicate urgent needs for equipment safety standards, professional development programs, curriculum innovation integrating Chinese cultural elements with contemporary OAE practices, and enhanced public communication about developmental benefits. This research contributes empirical evidence to the emerging literature on OAE camps in Asian contexts and provides actionable recommendations for improving youth camp quality in China’s rapidly expanding sector.